Assessment of a reconfiguration of the InterSpread Plus US national FMD model as a potential tool to analyze a foot-and-mouth disease outbreak on a single large cattle feedlot in the United States - Mielke, Sarah R.; Rigney, Columb; Hagerman, Amy D.; Boyer, Timothy C.; Delgado, Amy H.; Arzt, Jonathan; Holmstrom, Lindsey K. (Frontiers in Veterinary Science, 2023)
An incursion of foot-and-mouth disease (FMD) into the United States remains a concern of high importance and would have devastating socioeconomic impacts to the livestock and associated industries. This highly transmissible and infectious disease poses continual risk for introduction into the United States (US), due to the legal and illegal global movement of people, animals, and animal products. While stamping out has been shown to effectively control FMD, depopulation of large cattle feedlots (>50,000 head) presents a number of challenges for responders due to the resources required to depopulate and dispose of large numbers of animals in a timely and effective manner. However, evaluating alternative strategies for FMD control on large feedlots requires a detailed within-farm modeling approach, which can account for the unique structure of these operations. To address this, we developed a single feedlot, within-farm spread model using a novel configuration within the InterSpread Plus (ISP) framework. As proof of concept we designed six scenarios: i) depopulation -the complete depopulation of the feedlot, ii) burn-through -a managed "burn-through" where the virus is allowed to spread through the feedlot and only movement restriction and biosecurity are implemented, iii) firebreak-NVtargeted depopulation of infected pens and adjacent pens without vaccination; iv) firebreaktargeted depopulation of infected pens and adjacent pens with vaccination of remaining pens; v) harvest-NV -selective harvest of pens where a 100% movement restriction is applied for 28-30 days, then pens are set for selection to be sent to slaughter, while allowing a controlled "burn-through"